Bio-inspired adhesive hydrogel for wound healing - Wenzhao Li; Yuandong Zheng; Weiran Pang; Puxiang Lai (Biomedical Technology, 2023)
Wound healing introduces a series of interesting challenges in healthcare, such as open wounds, burn wounds, and chronic infection wounds. Hence more accurate and effective biomedical materials are expected, for which emerging hydrogels with unique and excellent properties have demonstrated great potential. When they are applied as wound dressings, tissue patches, plugging agent, drug carriers, and biosensors, etc., there are urgent requirements for adhesive capabilities. The existence of interfacial water, soft tissue and moving surfaces, safety, and harmlessness, however, constitutes major constraints for medical adhesive hydrogels. In nature, organisms often adhere through unique structures or specific chemical components, which stimulates inspirations for medical hydrogels to overcome the above challenges. In this review, we will classify adhesive hydrogels into glue-like adhesives and tape-like patches according to their form. First, this review will introduce the principles and design ideas of biomedical adhesive hydrogels. Then, as biomedical materials, the applications and effects of their interactions with organisms through adhesion will be summarized. Finally, this review will summarize the achievements, challenges, and future development of bio-inspired adhesive hydrogel towards wound healing.